A conceptual review of the effectiveness of flipped learning in vocational learners’ cognitive skills and emotional states - Zhou, Xiuqin (Frontiers in Psychology, 2023)
Flipped learning is a learner-centered and technology-driven approach that benefits from the inverted method of teaching. Recently, instructors have begun to employ innovative pedagogies like flipped learning approach, to change the conventional practices in vocational education. This review examined the effect of the flipped learning approach on vocational education. The earlier investigations showed the significant effect flipped learning approach on vocational learners’ emotions, such as engagement, motivation, self-efficacy, and their cognitive skills, including critical thinking, problem-solving, learning skill, learning strategies, and communicative competence. However, this review implicated that flipped learning, as a type of blended learning, may be beneficial for learners, instructors, material developers, school managers, and students' parents to be aware of this valuable learner-centered approach in vocational education.